A Cross-Sectional Survey of Emotional Intelligence Relating to Binge Eating Disorder in Unemployed Population - Sohail Hameed,, Maria Tahir, Muhammad Arshad Abbas,, Naeem Sarwar, Ghulam Hassan, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To examine the associations between emotional intelligence (EI) and Binge Eating Disorder (BED) with a mediating role played by post-traumatic stress disorder (PTSD) in the unemployed population, thus performance in an integrated manner. Study design: A Cross-sectional study Place and duration of Study: Rural and urban areas of Punjab, Pakistan during the months of December 2020-2021 Methodology: For this purpose, Wong and Law Emotional Intelligence Scale, Binge Eating Scale and PTSD Check List–Civilian Version was used to measure EI, BED, and PTSD score, respectively. The assumptions were tested using non-linear regression-based partial least squares path modelling (PLS-SEM). Results: The results revealed that unemployed individuals are at enhanced risk to develop BED. High levels of EI help to cope the stress of unemployment and overcome BED and vice versa. In this study, PTSD, a cause of unemployment, was found to be negatively related to EI and positively related to BED. However, no mediation of PTSD between EI and BED was observed. Conclusions: Our findings suggest that enhanced emotional abilities are directly associated with lower levels of work-related stress and BED. However, a diagnostic study is needed to validate the findings and establish BED diagnosis in individuals with low EI. This study helps in validation of emotional intelligence as a factor in the development of binge eating disorder. It helps in the development of programs based on prevention of binge eating disorder in unemployed population on the basis of emotional intelligence level understanding. Keywords: Unemployment, eating behaviour, emotional stability, stress disorder, mediation analysis